Leading Pharmaceutical Innovation : How to Win the Life Science Race /: How to Win the Life Science Race. ([2018]) - Gassmann, Oliver, 1967-; Schuhmacher, Alexander; Zedtwitz, Maximilian von, 1969-; Reepmeyer, Gerrit, 1976-
No abstract available